Effect of Acupressure on Cervical Ripening - Torkzahrani, Shahnaz (Iran Red Crescent Med J, 2015)
BACKGROUND: Cervical ripening is one of the main stages of initiation labor. Acupressure in Chinese medicine is considered as an invasive technique, which through reliving oxytocin ripens the cervix. Acupoint Sanyinjiao (SP6) was selected in this study because it is the acupoint selected in gynecology and it is easy for women to locate and apply pressure without medical assistance. OBJECTIVES: The aim of this study was to determine the effect of acupressure on cervical ripening. PATIENTS AND METHODS: In this randomized clinical trial, 150 primigravida with term pregnancy who had referred to Deziani hospital in Gorgan were chosen and divided to three groups: in the first group acupressure was done by the researcher while in the second groups this was performed by the mother her self, and the third group served as a control and only received routine care. For both intervention groups the pressure was applied on Sp6 for about 20 minutes during one to five days. Elements were checked from cervical ripening at 48 and 96 hours after intervention and at the time of hospitalization. The tools for gathering information included demographic characteristics and midwifery history questionnaire, daily records and follow up forms. Content validity was used for validity of tools. Reliability of the observation check-list and physical examination was confirmed by inter-rater scores (inter observer), and daily records by test-re-test. Data was analyzed by analysis of variance (ANOVA), Kruskal-Wallis and Chi-squared tests (P ≤ 0.05). RESULTS: There was a significant difference between mothers’ educations in the three groups. Most of the mothers (59.5%) in the researcher-performed acupressure group had secondary education. Cervical ripening was significantly different between the three groups after 48 hours (P ≤ 0.05), yet there was no significant difference after 96 hours and at the time of admission. Mean Bishop score was enhanced after 48 hours in the researcher-performed acupressure group (P ≤ 0.021) and the self-performed acupressure group (P ≤ 0.007) in comparison to the control group. CONCLUSIONS: The results showed that acupressure is a safe technique and leads to cervical ripening. Thus, regarding the desired results that were achieved when mothers applied acupressure themselves, it could be suggested that it is beneficial for mothers to be trained to apply this method at home.